Protective Effects of the Natural Sesquiterpene Lactones Against Damage Induced by Glutamate and Peroxide in SK-N-MC Cells - Dubrovskaya, E.S.; Semakov, A.V.; Afanasyeva, S.V.; Neganova, M.E.; Kozlovski, V.I.; Klochkov, S.G. (Biomedical Chemistry: Research and Methods, 2018)
An the present study we evaluated the effect of natural sesquiterpene lactones of plants of the genus Inula on the cells of neuroblastoma SK-N-MC under conditions of toxic stress induced by H2O2 and glutamate. Lactones increased cell survival under these conditions and the leader compounds were identified in this series. A putative mechanism for the protective action of lactones on cells under condition toxic stress has been proposed.